Teaching approaches employed in teaching literature component in english in urban and rural secondary schools - Ramlan, Najah
Literature component in English programme (LiEP) is included in the English language syllabus for all secondary schools in Malaysia, aiming at engaging students in reading literature for enjoyment and self-development. Different approaches to literature teaching can be used, ranging from teacher-centered approach to student-centered approach. However, it is difficult to implement these approaches when teaching literature component in the real English language classroom setting either in urban or rural secondary schools. Therefore, this study aims to identify the teaching approaches that English language teachers use when teaching literature in rural and urban secondary schools. Questionnaire was used in collecting the data from 20 secondary schools in Pontian and Johor Bahru districts. In this study, it was found that teacher-centered approach is used in rural secondary schools while student-centered approach is employed in urban secondary schools when teaching literature component.